Metode Group Investigation dan Role Playing untuk Optimalisasi Dialog Kerukunan di Denpasar - Muhayat, Imam (Proceedings of Annual Conference on Community Engagement, 2018)
Harmony as a unifying nation is the concern of multi-backgrounds. The mandate of PBM Number 9 and 8 of 2006 aims to realize harmony. The following up on the mandate of PBM, FKUB interconnected with Leading Sector, Kesbangpol Badung Regency held a Dissemination and Dialogue on Inter-Religious Harmony for Vocational High School Students in Badung Regency. To optimize harmony socialization, speakers using the investigation group, and role playing approach. Through the first approach, participants get enrichment of inquiry, knowledge, and dynamic of the learning group. The synergy of the second method can attract participants, so that the situation class becomes dynamic, enthusiastic, and communicative, so that the initiative, and visionary of creativity is built by itself. The method can also arouse passion and a spirit of optimism in the participants along with the growing sense of togetherness and high social solidarity. Force of acceptance from sincere nature, the willingness of the participants to be ready to carry out harmony actions, both at school and in the community. Recorded more than 95 percent, the results of the informant’s investigation of 70 participants present in each sub-district, and 150 participants who attended in the Inspectorate Room Badung Regency agreed, this kind of activity is a very important, because it was useful and very valuable to realize various interests in various life necessity. It’s a fact of the formation of a good personality for the participants recorded in the Socialization and Dialogue activities, when they finished the event shaked greetings with the organizing committee and the speakers with a polite, attitude as a form of their nobility.